Особенности управления частотой элктромагнитных колебаний системы радиоакустического зондирования атмосферы - Лисовой, Д. В. (ХНУРЕ, 2020)
A method of radio-acoustic sounding of the atmosphere is proposed, which makes it possible to fulfill the Bragg conditions during the propagation of an acoustic packet over the entire range of sounding heights.
Keywords: зондирование; подстройка частоты